Thermal reactor safety assessment proceedings of the conference organized by the British Nuclear Energy Society, held at Manchester on 23-26 May 1994. (British Nuclear Energy Society, 1994)
Aims to cover the practical application of all aspects of thermal reactor safety. This conference volume includes the proceedings of a major international conference on thermal reactor safety assessment. It is co-sponsored by the American Nuclear Society, the Atomic Energy Society of Japan, the British Nuclear Forum, and others.